MENINGKATKAN KESADARAN WISATAWAN DALAM MENJAGA KELESTARIAN EKOSISITEM WISATA PANTAI BAHARI DI KECAMATAN JAWAI SELATAN - Farmiansyah, Eko; Asrin, Asrin; Danil, Danil; Pandika, Edo; Ervandi, Ervandi; Rosada , Fadia; Ramadhan, Fadzri; Hafizin, Hafizin; Hidayat , Rahmat; Nadika , Robby Mulya; Maulana, Tan Dede; Agam, Beryaldi; Sangkala, Sangkala (PUSAT PENELITIAN DAN PENGABDIAN PADA MASYARAKAT (PPPM) POLITEKNIK NEGERI SAMBAS, 2023)
One of the tourist attractions that attracts the attention of domestic and foreign tourists is the marine beach in Kec. South Java. Looking at the history of this Marine Tourism Beach, it has been around for a long time, this beach is an empty beach and forest that is not managed or developed, since 2019 one of the residents of Jawai Laut Village has taken the initiative to invite local residents to explore this still beautiful beach and form an awareness group. Marine Tourism Beach tourism which has 52 members. The aim of this background is to increase tourist awareness in preserving the marine coastal tourism ecosystem in the Javai Laut village, Javai sub-district. The methods used in the activity include counseling and discussion. Based on outreach activities at the maritime coast of Jawai Laut Village, Kec. This outreach program conveys information regarding tourist awareness in preserving the marine coastal tourism ecosystem in Jawai Laut village, Jawai sub-district the tourists were very enthusiastic in taking part in the outreach that was carried out.